2013
DOI: 10.1007/s00348-013-1494-6
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent swirling flow in a model of a uniflow-scavenged two-stroke engine

Abstract: The turbulent and swirling flow of a uniflowscavenged two-stroke engine cylinder is investigated using a scale model with a static geometry and a transparent cylinder. The swirl is generated by 30 equally spaced ports with angles of 0°, 10°, 20°, and 30°. A detailed characterization of the flow field is performed using stereoscopic particle image velocimetry. Mean fields are calculated using both a fixed coordinate system and a coordinate system based on the instantaneous flow topology. Timeresolved measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…It is found that none of the ensemble-averaged velocities display any significant change between the use of Method One or Method Two. This finding reveals that the wandering motion of vortex center has little effect on the ensemble-averaged velocity, which is consistent with the finding in the study of Ingvorsen et al 19 that ensemble-averaged velocity profiles of swirling flow obtained at a fixed frame could well represent the key flow features for a small wandering motion. Figure 6a shows normalized mean radial velocity ⟨u r ⟩/U j as a function of radial position for all four planes.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…It is found that none of the ensemble-averaged velocities display any significant change between the use of Method One or Method Two. This finding reveals that the wandering motion of vortex center has little effect on the ensemble-averaged velocity, which is consistent with the finding in the study of Ingvorsen et al 19 that ensemble-averaged velocity profiles of swirling flow obtained at a fixed frame could well represent the key flow features for a small wandering motion. Figure 6a shows normalized mean radial velocity ⟨u r ⟩/U j as a function of radial position for all four planes.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…The present work extends the work by Ingvorsen et al (2013) by considering the flow in the engine model under dynamic conditions, where the ports are opened and closed by the piston. The main purpose of the present work is to establish a database of reliable data that can be used in the development and validation of CFD models.…”
Section: Present Workmentioning
confidence: 73%
“…The swirling in-cylinder flow in uniflow-scavenged engines has been the subject of earlier works. Investigations have been based on both CFD (Sung and Patterson 1982;Diwakar 1987;Uzkan 1988;Goldsborough and Blarigan 2003;Obeidat et al 2014;Sigurdsson et al 2014) and experiments (Percival 1955;Nakagawa et al 1990;Sher et al 1991;Haider et al 2013;Ingvorsen et al 2012Ingvorsen et al , 2013. Due to the costs and limitations of experimental investigations on full-scale engines, the majority of the experimental work have been performed on simplified scale models, and often under steady-flow conditions.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…24 CFD offers an expedient means for investigating the flow, gas exchange, and combustion processes under realistic engine operating conditions and identification of important features and major underlying interactions between them. 25 Although OP2S engine has already been commonly modeled and tested by many researchers, most of these researches focus on the basic engine performance; they are unable to identify details of the engine design and operating parameters. The article provides some insights into multi-dimensional gas flows in scavenging process of OP2S-GDI engine using commercial CFD software AVL-FIRE based on numerically simulated OP motion profiles and evaluates the scavenging performance using different design and operating parameters, namely, OP motion phase difference and crank-connecting rod ratio.…”
Section: Introductionmentioning
confidence: 99%